A situational analysis of tobacco control in Ghana: progress, opportunities and challenges - Arti Singh; Ellis Owusu-Dabo; Fiona Dobbie; Noreen Mdege; Ann McNeill; John Britton; Linda Bauld (Journal of Global Health Reports)
Tobacco use is the leading cause of preventable deaths in the world, with most of these deaths now occurring in low and middle-income countries (LMICs). Sub-Saharan Africa (SSA) is at an early stage of a tobacco epidemic and is, therefore, particularly vulnerable to rapid growth in tobacco consumption. More than a decade into the implementation of the World Health Organization's Framework Convention on Tobacco Control (FCTC), State Parties in several countries in SSA, such as Ghana, have yet to fully fulfil their obligations. Despite early ratification of the FCTC in 2004, progress in implementing tobacco control measures in Ghana has been slow and much work remains to be done. The aim of this paper is to critically reflect on tobacco control implementation in Ghana, identify significant research priorities and make recommendations for future action to support tobacco control implementation. We emphasize the need for stronger implementation of the FCTC and its MPOWER policy package, particularly in the area of tobacco taxes, illicit trade and industry interference.